Epigenetics regulates transcription and pathogenesis in the parasite Trichomonas vaginalis - Pachano, Tomas (2017)
Trichomonas vaginalis is a common sexually transmitted parasite that colonizes the human urogenital tract. Infections range from asymptomatic to highly inflammatory, depending on the host and the parasite strain. Different T. vaginalis strains vary greatly in their adherence and cytolytic capacities. These phenotypic differences might be attributed to differentially expressed genes as a consequence of extra-genetic variation, such as epigenetic modifications. In this study, we explored the role of histone acetylation in regulating gene transcription and pathogenesis in T. vaginalis. Here, we show that histone 3 lysine acetylation (H3KAc) is enriched in nucleosomes positioned around the transcription start site of active genes (BAP1 and BAP2) in a highly adherent parasite strain; compared with the low acetylation abundance in contrast to that observed in a less-adherent strain that expresses these genes at low levels. Additionally, exposition of less-adherent strain with a specific histone deacetylases inhibitor, trichostatin A, upregulated the transcription of BAP1 and BAP2 genes in concomitance with an increase in H3KAc abundance and chromatin accessibility around their transcription start sites. Moreover, we demonstrated that the binding of initiator binding protein, the transcription factor responsible for the initiation of transcription of ~75% of known T. vaginalis genes, depends on the histone acetylation state around the metazoan-like initiator to which initiator binding protein binds. Finally, we found that trichostatin A treatment increased parasite aggregation and adherence to host cells. Our data demonstrated for the first time that H3KAc is a permissive histone modification that functions to mediate both transcription and pathogenesis of the parasite T. vaginalis.